COMPARATIVE ANALYSIS OF THE HIGHER EDUCATION ACCREDITATION SYSTEMS OF THE REPUBLIC OF ARMENIA AND THE RUSSIAN FEDERATION (Education in the 21st Century, 2023)
The article touches upon the accreditation systems for higher education of the Republic ofArmenia (RA) and the Russian Federation (RF). Evolutions and development perspectives of theaccreditation system of RA and RF have been analyzed, and a comparative analysis has beenconducted.Generalizing the practice of accreditation in the system of higher education in RA and RF,we note the basic differences:1. Armenian accreditation agency - National Center for Professional Education QualityAssurance (ANQA) is functionally independent. Russian accreditation agency - NationalAccreditation Agency (NAA) is a governmental structure.2. The model of state accreditation operating in the RA functions in the form of mandatoryinstitutional accreditation and voluntary program accreditation, whereas the Russian Federation ispracticing program accreditation.3. In contrast to the Republic of Armenia, where only the institute of state accreditationoperates with the only accreditation agency ANQA, in the Russian Federation, the institutes ofpublic and professional-public accreditation are also developed, and the most famouscorresponding accreditation agencies, The Agency for Quality Assurance in Higher Education andCareer Development ( AKKORK ) and the National Accreditation Center are introduced alongwith NAA in European Association for Quality Assurance in Higher Education (ENQA) and areincluded, in contrast to the NAA, into the register, The European Quality Assurance Register forHigher Education (EQAR). Note that ANQA also has membership in ENQA and is included in theEQAR register.1334. There are numerous differences in the procedure for conducting an accreditationexpertise. The RF does not provide the institution of appeal against decisions of state accreditationeither.5. The higher education accreditation system of the RA is based on the compliance withStandards and Guidelines for Quality Assurance in the European Higher Education Area (ESG).The situation is different in the model of state accreditation of the Russian Federation.Although the quality assurance systems of the RA and the Russian Federation differ in theforms of organization of the respective structures and in the chosen models of accreditation, theagreement on cooperation and interaction between NAA and ANQA signed in June 2016 can serveas a basis for further harmonization of the accreditation systems of the RA and the RF.